Pengaruh Pengelolaan keuangan dan pemahaman SAK EMKM terhadap kinerja keuangan UMKM sektor makanan di kabupaten Tasikmalaya - Evi Nurapifah (UNIVERSITAS DHARMAWANGSA, 2026)
Micro, Small, and Medium Enterprises (MSMEs) constitute a strategic sector in supporting economic growth and employment in Indonesia. However, various challenges related to financial management and the understanding of Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) remain prevalent among MSME actors, potentially affecting their financial performance. This study aims to analyze the influence of financial management and understanding of SAK EMKM on the financial performance of food-sector MSMEs in Tasikmalaya Regency. The study employed a quantitative approach with an associative research design. Primary data were collected through questionnaires distributed to 100 MSME owners selected using purposive sampling techniques. Data analysis was conducted using multiple linear regression analysis with the assistance of SPSS version 26. The results indicate that financial management has a positive and significant effect on the financial performance of MSMEs, as evidenced by a significance value of 0.005 (< 0.05). In contrast, the understanding of SAK EMKM does not have a significant effect on financial performance, as indicated by a significance value of 0.281 (> 0.05). Furthermore, the coefficient of determination test shows that financial management and understanding of SAK EMKM jointly explain 25.4% of the variation in MSME financial performance, while the remaining 74.6% is influenced by other factors outside the scope of this study. These findings suggest that effective financial management plays a crucial role in improving MSME financial performance, whereas an understanding of SAK EMKM alone is insufficient to enhance financial performance without consistent implementation in business practices.